STREAMFINDER II: A possible fanning structure parallel to the GD-1 stream in Pan-STARRS1. Issue 3 (18th May 2018) - Malhan, Khyati; Ibata, Rodrigo A; Goldman, Bertrand; Martin, Nicolas F; Magnier, Eugene; Chambers, Kenneth
ABSTRACT: STREAMFINDER is a new algorithm that we have built to detect stellar streams in an automated and systematic way in astrophysical datasets that possess any combination of positional and kinematic information. In Paper I, we introduced the methodology and the workings of our algorithm and showed that it is capable of detecting ultra-faint and distant halo stream structures containing as few as ∼15 members (ΣG ∼ 33.6 mag arcsec −2 ) in the Gaia dataset. Here, we test the method with real proper motion data from the Pan-STARRS1 survey, and by selecting targets down to r 0 = 18.5 mag we show that it is able to detect the GD-1 stellar stream, whereas the structure remains below a useful detection limit when using a Matched Filter technique. The radial velocity solutions provided by STREAMFINDER for GD-1 candidate members are found to be in good agreement with observations. Furthermore, our algorithm detects a ${\sim } 40^{^° }$ long structure approximately parallel to GD-1, and which fans out from it, possibly a sign of stream-fanning due to the triaxiality of the Galactic potential. This analysis shows the promise of this method for detecting and analysing stellar streams in the upcoming Gaia DR2 catalogue.